2002
DOI: 10.1081/iph-120016050
|View full text |Cite
|
Sign up to set email alerts
|

FISH IMMUNOLOGY. I. BINDING AND ENGULFMENT OFCANDIDA ALBICANSBY ERYTHROCYTES OF RAINBOW TROUT (SALMO GAIRDNERIRICHARDSON)

Abstract: The role of fish erythrocytes (FE) as phagocytic cells has poorly been investigated, until now. Here, we have focussed our attention on the interplay between rainbow trout (Salmo gairdneri Richardson) erythrocytes and Candida albicans (CA). At the same time, the intervention of autologous head kidney macrophages (MO) in the CA processing by FE has been studied. Data show that CA particles bind to FE, which, in turn, are able to engulf but not kill them. In the presence of MO, a decrease of FE with bound CA occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 22 publications
6
36
0
2
Order By: Relevance
“…Erythrocytes can induce blood B cells to produce immunoglobulin through proliferation, differentiation and maturity (Boackle et al, 1998) and has been shown to actively form rosettes to facilitate the clearance of pathogens by macrophages (Passantino et al, 2002), while leucocytes can migrate in response to inflammatory stimuli (Carroll, 2004). Hemoglobin is an important source of bioactive peptides that have been shown to participate in the innate immune response and participate in the killing of invading microbes (Bishlawy, 1999;Jiang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocytes can induce blood B cells to produce immunoglobulin through proliferation, differentiation and maturity (Boackle et al, 1998) and has been shown to actively form rosettes to facilitate the clearance of pathogens by macrophages (Passantino et al, 2002), while leucocytes can migrate in response to inflammatory stimuli (Carroll, 2004). Hemoglobin is an important source of bioactive peptides that have been shown to participate in the innate immune response and participate in the killing of invading microbes (Bishlawy, 1999;Jiang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of fish to diazinon polluted water caused pathological changes in fish and activated the monocytesemacrophage [28]. The innate immune response of Nile tilapia to these OPs was evaluated through the determination of two phagocytic parameters: PI and %AC.…”
Section: Discussionmentioning
confidence: 99%
“…Within melanomacrophage centres, macrophages have been shown to destroy and kill the fungus Candida albicans but also to phagocytose rainbow trout erythrocytes in the immediate vicinity (Passantino et al 2002). Consequently, melanomacrophage centers seem to play an important role in the elimination of foreign particulate material and of fish erythrocytes that have ingested microorganisms.…”
Section: Discussionmentioning
confidence: 99%